New endemic familial parkinsonism in south Moravia, Czech Republic and its genetical background. Issue 38 (September 2018) - Bartoníková, Tereza; Menšíková, Kateřina; Kolaříková, Kristýna; Vodička, Radek; Vrtěl, Radek; Otruba, Pavel; Kaiserová, Michaela; Vaštík, Miroslav; Mikulicová, Lenka; Ovečka, Josef; Šáchová, Ludmila; Dvorský, František; et al.
Abstract : Abstract: An increased prevalence of familial neurodegenerative parkinsonism or cognitive deterioration was recently found in a small region of southeastern Moravia. The aim of the study was to assess the genetic background of this familial disease. Variants in the ADH1C, EIF4G1, FBXO7, GBA + GBAP1, GIGYF2, HTRA2, LRRK2, MAPT, PRKN, DJ-1, PINK1, PLA2G6, SNCA, UCHL1, VPS35 genes were examined in 12 clinically positive probands of the pedigree in which familial atypical neurodegenerative parkinsonism was identified in previous epidemiological studies. Libraries were sequenced by massive parallel sequencing (MPS) on the Personal Genome Machine (PGM; Ion Torrent). Data were analyzed using Torrent Suite and IonReporter software. All variants were then verified and confirmed by Sanger sequencing. We identified 31 rare heterozygous variants: 11 missense variants, 3 synonymous variants, 8 variants in the UTR region, and 9 intronic variants. Six variants (rs1801334, rs33995883, rs35507033, rs781737269, rs779760087, and rs63750072) were evaluated as pathogenic by at least one in-silico predictor. No single "founder" pathogenic variant associated with parkinsonism has been found in any of the probands from researched pedigree. It may rather be assumed that the familial occurrence of this disease is caused by the combined influence of several "small-effect" genetic variants that accumulate in the population with long-lasting inbreeding behavior.